PENGARUH KNOWLEDGE LEADERSHIP, KOMUNIKASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT VALADOO INDONESIA - Oktavianna, Rakhmawati (Universitas Pakuan, 2018)
Employee performance is considered important for organizations due to the success of an organization influenced by it. Job performance or achievement is the job result which accomplished by an employee in performing tasks according to the responsibility given to him. A common problem that must be considered in the company is related with job performance. Without good employeeâs performance at PT Valadoo Indonesia, its excellence is not going to happen. One of the factors that can be used to improve the employeeâs performance is knowledge leadership , communication and motivation. Leaders who have a good knowledge and experience will be able to improve the performance of employees in achieving the companys vision and mission. In carrying out the work, the employee can not be separated from communication with fellow co-workers, the boss and the subordinate. Good communication can be an appropriate means to improve employee performance. In addition to communication, it is also necessary if the motivation for employees with high work motivation usually has a peak performance. Therefore, Â what is the effect of knowledge of leadership, communication and motivation on employee performance at PT Valadoo Indonesia either partially or simultaneously. The aim of the study is to identify and analyze the effect of knowledge of leadership, communication and motivation on employee performance PT Valadoo Indonesia. The theory used in this study is theoris of human resource management, especially those related to knowledge leadership, communicatio, motivation and performance of employees. Population Â used in this study is the employee of PT Valadoo Indonesia, Â male and female, 150 people. Sampling technique used is simple random sampling. Method of data collection is using questionnaire data analysis that is Structural Equation Modeling ( SEM ) of Lisrel 8.7.Â Keywords: Knowledge Leadership, Communication, Motivation and Performance of Employees